Cover Feature: Nickel‐Catalyzed Aminofluoroalkylation of Alkenes: Access to Difluoroalkylated N‐Containing Heterocyclic Compounds (Eur. J. Org. Chem. 1/2022). Issue 1 (4th January 2022) - Fu, Xiaoyi; Zhang, Tianyu; Wu, Jingjing; Sun, Yijie; Wu, Fanhong
Abstract : The Cover Feature shows the nickel‐catalyzed aminofluoroalkylative cyclization reaction with unactive alkenes and iododifluoromethyl ketones for the synthesis of difluoroalkyl cyclic amines. The stone in the picture represents the flask filled with two reaction substrates. The Ni sword is the catalyst used to activate and accelerate the reaction, delivering the target compounds difluoroalkyl cyclic amines. More information can be found in the Full Paper by J. Wu, F. Wu et al .